2012
DOI: 10.5539/ibr.v5n12p119
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Regional Distribution of FDI Inflows across China’s Four Regions

Abstract: This paper performs an empirical assessment of China's inward FDI by analysing the relative importance of the potential determinants of FDI inflows across the four regions of China for the period 2001-2009. The determinants examined are: Market size, labour cost, labour quality, physical infrastructure development, telecommunication, degree of economic openness and government incentives to attract FDI. Our paper employs a multiple regression model for each region and then compares the results across four regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 5 publications
3
20
0
Order By: Relevance
“…The higher GDP and INDEX values indicate that more foreign funds are required to increase TDI in China. This finding is in agreement with the findings reported by Sun et al (2002) and Liu et al (2012).…”
Section: Regression Analysessupporting
confidence: 94%
See 2 more Smart Citations
“…The higher GDP and INDEX values indicate that more foreign funds are required to increase TDI in China. This finding is in agreement with the findings reported by Sun et al (2002) and Liu et al (2012).…”
Section: Regression Analysessupporting
confidence: 94%
“…Taiwanese FDI enterprises investing in high-technology electronic industries capitalized on the tax rate 15%, and TDI in high-technology electronics industries increased; thus, H3 is supported. This finding is consistent with the results reported by Liu et al (2012). Table 5 shows the variables for controlling the effect of nontax factors on TDI.…”
Section: Regression Analysessupporting
confidence: 91%
See 1 more Smart Citation
“…Another study by Liu et al (2012a) in China offers various descriptions. For example, they find that market size becomes a priority factor for the FDI inflow to the coastal areas and eastern coastal area, whereas the level of the openness becomes the most important factor for the FDI inflow in the middle-land areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Foster (2011) found that FDI in mainland China is heavily skewed in favor of the richest east region, while the west region is the weakest attractor. Liu et al (2012) analyzed the relative importance of the potential determinants of FDI inflows across the four regions of China for the period 2001-2009. The determinants examined were: market size, labor cost, labor quality, physical infrastructure development, telecommunication, and degree of economic openness and government incentives to attract FDI.…”
Section: The Operating Efficiency Of Fdi In Mainland Chinamentioning
confidence: 99%